Association Between Maternal Factors and Stunting Based on the Indonesia Family Life Survey 5 (IFLS-5) - Sukamto, Charissa Otniel; Fatimah, Siti Nur; Indraswari, Noormarina (Makara Journal of Health Research, 2026)
Background: Stunting remains a major issue in Indonesia. Maternal factors during pregnancy are one of the key determinants in preventing stunting. This study aimed to analyze the association between maternal history during pregnancy (age, height, parity, and inter-pregnancy interval) and stunting, with a comparison between urban and rural areas. Methods: This analytical cross-sectional study used data from 3,639 children aged 1-5 years old from the household survey of Indonesia Family Life Survey 5, conducted between late October 2014 and August 2015 within 13 provinces in Indonesia. Data was analyzed using chi-square and binary logistic regression methods. Results: The toddlers were predominantly boys (51.9%), with a mean age of 3 years (1–5). Around 37% were stunted. Stunting was associated with adolescent mothers, short maternal stature, high parity, and rural residence. In both urban and rural areas, these maternal factors were significantly associated with stunting. Conclusions: Younger maternal age, lower maternal height, and high parity were significant predictors of stunting, including in both urban and rural areas. Stunting management strategies should prioritize reducing early pregnancy, improving maternal nutrition, and limiting high parity with equitable implementation across rural areas to address existing disparities in Indonesia.